SOCS Proteins in Immunity, Inflammatory Diseases, and Immune-Related Cancer - Sobah, Mohamed Luban; Liongue, Clifford; Ward, Alister C. (Frontiers in Medicine, 2021)
Cytokine signaling represents one of the cornerstones of the immune system, mediating the complex responses required to facilitate appropriate immune cell development and function that supports robust immunity. It is crucial that these signals be tightly regulated, with dysregulation underpinning various immune defects, including excessive inflammation and immune-related malignancies. A specialized family of proteins called suppressors of cytokine signaling (SOCS) participate in negative feedback regulation of cytokine signaling ensuring it is appropriately restrained. The eight SOCS proteins identified regulate cytokine and other signaling pathways in unique ways. SOCS1-3 and CISH are most closely involved in the regulation of immune-related signaling, influencing processes such polarization of lymphocytes and the activation of myeloid cells by controlling signaling downstream of essential cytokines such as IL-4, IL-6 and IFN-. SOCS protein perturbation disrupts these processes resulting in the development of inflammatory and autoimmune conditions, immune deficits as well as immune-related malignancies. As a consequence, SOCS proteins are garnering increased interest as a unique avenue to treat these disorders.